A META-META-ANALYSIS OF THE IMPACT OF COVID-19 ON PREGNANT WOMEN - THAITHAE, SUPARP; THANABOONPUANG, PARINYAPORN; PHUTONG, PIANGKHUAN; CHAIYO, SASIPRIYA (International Journal of Allied Health Sciences, 2025)
Introduction: There are many studies on the effects of COVID-19 on pregnant women. Providing comprehensive evidence on physical, psychological, and fetal effects, so that the knowledge gained can be applied to the care of pregnant women and their infants. This study aimed to conduct a meta-meta-analysis of the impact of COVID-19 on pregnant women and their infants. Methods: This meta-meta-analysis encompasses 21 meta-analyses identified via search in electronic databases (PubMed, CINAHL). Meta-analyses had to report the effects of coronavirus disease 19 (COVID-19) on pregnant women and neonates. Analyses were based on random effects models. To combine results, the effect estimates of the meta-analyses were transformed to SMD and weighted to correct primary study overlap, conducted by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (AMSTAR2) and analyzed the data using the meta-analysis website. The sample of meta-analyses included 21 meta-analyses (total number of studies k = 914, n = 3,936,822). Results: the effect of COVID-19 affected depression (EF = 21.74(95% CI 13.84 – 34.15) p <.01, I2 = 97%, p <.01), anxiety (EF = 23.77(95% CI 14.71 – 38.42) p <.01, I2 = 89%, p <.01. But COVID-19 does not statistically significantly affect the health of pregnant women and infant. Conclusion: Therefore, in addition to taking care of the physical health of pregnant women infected with COVID-19, mental health should also be given importance.